Optimizing Urban Drainage Systems to Cope with Continuous Flooding - Amin Zaki; Nurul Huda; Syafiq Amir (Yayasan Adra Karima Hubbi, 2024)
Urban flooding has become a significant challenge in many cities worldwide, exacerbated by climate change, rapid urbanization, and inadequate drainage systems. Effective management of urban drainage is crucial for mitigating flood risks and enhancing resilience in urban environments. This research addresses the pressing need for optimized drainage systems to respond to sustained flooding events. The study aims to evaluate and optimize urban drainage systems to improve their efficiency in flood management. It seeks to identify key factors influencing drainage performance and propose strategies for enhancement. A mixed-methods approach was employed, combining quantitative modeling and qualitative assessments. Hydraulic models were developed to simulate drainage system performance under various rainfall scenarios. Additionally, interviews with urban planners and engineers were conducted to gather insights on current challenges and potential solutions. The findings reveal that many urban drainage systems are operating below their optimal capacity, leading to frequent flooding during heavy rainfall events. Key factors identified include insufficient infrastructure, poor maintenance practices, and lack of integrated planning. The research proposes a set of optimization strategies, including the implementation of green infrastructure and improved maintenance protocols. The study concludes that optimizing urban drainage systems is essential for effectively managing urban flooding. Policymakers and urban planners must prioritize investments in drainage infrastructure and adopt innovative strategies to enhance resilience against flooding. Future research should focus on long-term monitoring and evaluation of implemented solutions to ensure ongoing effectiveness in flood management.